Human papillomavirus DNA detection in cervical samples from women of reproductive age in Mogadishu, Somalia - Bashiru Garba; Maryan A Sh Nur; Maryam Adawe; Mohamed H Adam; Jamal H Mohamoud; Hassan A Dahie; Mohamed M Ahmed; Abdirahman K Mohamud; Sadio A Mohamed; Fartun AH Orey; Jihaan Hassan; Hodo A Asowe; et al. (Journal of Infection in Developing Countries)
Introduction: Somalia is among the countries with a high burden of human papillomavirus (HPV) infection in Sub-Saharan Africa. In 2022, 660,000 infections are reported among women globally, out of which 350,000 died from the disease. Most of the studies on HPV reported from Somalia are based on cytologic analysis which is a subjective and suboptimal assessment. The recent World Health Organization (WHO) guidelines for HPV recommend DNA-based testing as a better alternative to the traditional pap smear test.